Crack initiation behavior of notched specimens on heat resistant steel under service type loading at high temperature (Fracture and Structural Integrity, 2016)
Cracks at notches deserve special consideration in the design of steam turbine components. This work is addressed to investigate the crack initiation behavior a 10%Cr rotor steel with the help of notched specimensunder service-type loading. A significant drifting down of the peak-values of axial deformation under constant amplitude load was observed. Crack initiation was evaluated with the help of the relationship between irreversible deformation energy and cycle number. Further, metallographic examinations were employed to characterize the superposition of creep and fatigue damage mechanisms. Both Neuber-hypothesis and von Mises equivalent strain at notch root were applied for lifetime prediction. Finally, the effectiveness ofboth methods is validated by comparing with experimental results.
Keywords: 10%Cr steel; Notched; Lifetime; Neuber; von Mises